LEGAL REVIEW OF THE ISSUANCE OF STATEMENT OF ABILITY TO MANAGE AND MONITOR THE ENVIRONMENT OF MSMEs BASED ON THE REGULATION - Ainun Nisha; Ratu Mawar Kartina; Endang Sutrisno; Diky Dikrurrahman; Raden Handiriono (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
The development of wood industry SMEs in the Mundu District, Cirebon Regency is certainly a concern in making environmental permits so that their businesses and/or activities do not cause environmental pollution. In this case, many MSME entrepreneurs in the wood industry do not have a Statement of Ability to Manage and Monitor the Environment (SPPL). The implementation of the SPPL permit process is not optimal because many SMEs in the Wood Industry have difficulty understanding SPPL. With the government's handling of the wood industry MSME business actors who do not have an SPPL permit, it is hoped that it can minimize the occurrence of environmental pollution by the Wood Industry MSME business actors. The research method used is the empirical juridical method. The implementation of the SPPL permit process carried out by the Wood Industry MSMEs has not been optimal because many business actors of the Wood Industry MSMEs do not understand about SPPL due to technological factors and the lack of socialization from the government. The government's handling of the Wood Industry MSME business actors who do not yet have an SPPL is by giving a written warning until the temporary suspension of their activities and/or business until the Wood Industry MSME business actor makes an SPPL.